Pendidikan Karakter Berbasis Islam: Strategi Kebijakan Dalam Membentuk Generasi Berakhlak - Eli Sabrifha (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the strategy of Islamic-based character education policies in shaping a generation with moral character amidst a moral crisis. Using qualitative literature study methods, this study examines government policies, journals, books, and trusted media reports through a documentation approach and systematic searches on Google Scholar, Garuda, and the Ministry of Religious Affairs portal. Data are analyzed thematically with a focus on the concept of character education, policy implementation, and implementation challenges. The results show that although the government has launched programs such as the Character Education Strengthening Movement (PPK) and religious moderation, their implementation is still hampered by a lack of policy integration between the Ministry of Education, Culture, Research, and Technology and the Ministry of Religious Affairs, minimal coordination, and overlapping training and evaluation. Furthermore, the role of teachers as agents of change is suboptimal due to the dominance of theoretical learning methods and a lack of training in contextual approaches. The implementation of character education is often ceremonial, without an integrated moral evaluation system. In conclusion, the effectiveness of Islamic-based character education requires synergistic policy integration, strengthening teacher competencies, and a holistic approach that addresses the affective and psychomotor dimensions. Thus, character education can transform from merely an administrative activity into a real and sustainable moral formation process. Abstrak Penelitian ini bertujuan menganalisis strategi kebijakan pendidikan karakter berbasis Islam dalam membentuk generasi berakhlak di tengah krisis moral. Menggunakan metode studi literatur kualitatif, penelitian ini mengkaji kebijakan pemerintah, jurnal, buku, dan laporan media terpercaya melalui pendekatan dokumentasi dan pencarian sistematis di Google Scholar, Garuda, dan portal Kemenag. Data dianalisis secara tematik dengan fokus pada konsep pendidikan karakter, implementasi kebijakan, dan tantangan pelaksanaan. Hasil menunjukkan bahwa meskipun pemerintah telah meluncurkan program seperti Gerakan Penguatan Pendidikan Karakter (PPK) dan moderasi beragama, implementasinya masih terkendala oleh ketidakpaduan kebijakan antara Kemendikbudristek dan Kemenag, minimnya koordinasi, serta tumpang tindih dalam pelatihan dan evaluasi. Selain itu, peran guru sebagai agen perubahan belum optimal karena dominasi metode pembelajaran yang teoritis dan kurangnya pelatihan dalam pendekatan kontekstual. Pelaksanaan pendidikan karakter pun kerap bersifat seremonial, tanpa sistem evaluasi akhlak yang terintegrasi. Kesimpulannya, efektivitas pendidikan karakter berbasis Islam memerlukan integrasi kebijakan yang sinergis, penguatan kompetensi guru, serta pendekatan holistik yang menyentuh dimensi afektif dan psikomotorik. Dengan demikian, pendidikan karakter dapat bertransformasi dari sekadar kegiatan administratif menjadi proses pembentukan moral yang nyata dan berkelanjutan.